The Application of Brain Organoids: From Neuronal Development to Neurological Diseases - Shou, Yikai; Liang, Feng; Xu, Shunliang; Li, Xuekun (Frontiers in Cell and Developmental Biology, 2020)
Brain organoids are derived from induced pluripotent stem cells and embryonic stem cells under 3-dimensional culture condition. The generation of organoid requires the self-assemble of stem cells, progenitor cells and multiple types of differentiated cells. Organoids display structures that resemble defined brain regions, and simulates specific changes of neurological disorders, thus become an excellent model for investigating brain development and neurological diseases. In the present review, we summarized the recent advances of the methods of culturing brain organoids, and the applications of brain organoids in investigating neurodevelopmental and neurodegenerative diseases.